(untitled) (European Journal of Marketing and Economics, 2020)
We witness unprecedented turn to the digital marketing. International Marketing, as a specific field of the marketing science, is no exception of the general trend. In this article, the trendsetters are presented, but also a different approach is followed. It is argued that the new metrics should be taken into consideration, but at the same time, the sustainable knowledge should not be neglected, because the traditional knowledge should work in conjunction with the newly appeared marketing tools. What is more, the “new” metrics are often built on the solid foundation of prior knowledge, which every marketing professional should be armed with.